Pojok Literasi untuk Remaja Masjid di Desa Batu Belah, Kampar Riau: Literacy Corner for the Mosque Youth Community in Batu Belah Village, Kampar, Riau - Basista, Ronny; Moekahar, Fatmawati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The partner of this Service was a mosque youth community in Batu Belah Village, Kampar, Riau. While the characteristics of the population in this village are relatively homogeneous, their problems are instead heterogeneous, especially those faced by its teenagers. The crime rate has been moderately high, with types of juvenile delinquency, drug abuse, theft, and decreased school motivation. Like elsewhere, the teenagers of this village are also suffering from gadget addiction. To this end, this Service aimed to help solve those problems by aligning the community's peace and upgrading social facilities. Establishing the Literacy Corner was one of the solutions by which the teenagers will gain literacy skills and improve their knowledge. The three Literacy Corner programs are: (1) establishing a reading corner, (2) selecting Reading Ambassadors from the teenagers, and (3) conducting a seminar on Digital Media Literacy. The ultimate goal of this Service was to build the habit of good literacy among Batu Belah Village teenagers, enhance the youth community's empowerment and generally minimise the problems weighed by the residents of Batu Belah Village, Kampar Riau.